Community Environmental Management to Create Jobs and Generate Income in Krasang District, Buriram Province, Thailand - Panoram, Preecha; Srisuk, Kulganya; Suphakritsuwannakul, Nitiroj; Jantaraj, Bancha (Journal of Ecohumanism, 2024)
This research aimed to study the environmental conditions, management and guidelines for community environmental management to create jobs and generate income in the community to solve poverty problems in Krasang District, Buriram Province. The researcher used the sample group according to the Taro Yamane table getting the 400 people. The research instruments were questionnaires. The statistics used for the research were percentage, mean, standard deviation, T-Test and F-Test. The research results found that the most common community environment was the garbage consisting of plastic, coffee or ovaltine bottles and sachets, soft drink cans, wet garbage, dry garbage and electronic waste. The community environmental management to generate income in the community included the waste management for transformation getting the highest mean (4.54). However, when considering the details, it was found that the first rank was the providing of knowledge on making consumer goods from plastic waste as a career. When classified by gender, there were no different opinions. When comparing residents who had lived in the community for a long time, only opinions on waste management were found significantly to have no different opinions at the .05.